Strategies for Effective Integration of Management Information System in Secondary Schools: Teachers’ Perspective from Awka Education Zone in Anambra State - Ogochukwu, Anike Dorathy (BOHR International Journal of Advances in Management Research, 2023)
This study looked into effective integration of management information system (MIS) in secondary schools in Awka Education Zone in Anambra State. The study was guided by three research questions and two hypotheses tested at the 0.05 level of significance based on a descriptive survey research approach. The sampling technique adopted was purposive type in order to focus on a determined specialized number of respondents. The study’s sample size was 130 secondary school teachers. A researcher-created questionnaire was used to gather the data. The tool was rigorously evaluated by two experts. When the instrument’s internal consistency was examined using Cronbach’s alpha, a reliability value of 0.88 was found. A t-test was used to assess the hypotheses after arithmetic mean and standard deviation scores were used to analyze the data. The findings demonstrated that the MIS assists the school in managing tests, enrolments, and fees by providing different people with password protection. The findings further revealed that MIS opportunities and needs should be identified and prioritized according to educational objectives rather than technical criteria. In addition, there is no significant difference in the male and female teachers’ knowledge about MIS in secondary schools. The implications of the study were drawn and recommendations proffered.